Wastewater Treatment in Tubular Photobioreactors: Exploring the Impact of Support Medium - Santos, Thalita Lacerda Dos; Belasco, Gabriela Costa [UNESP]; Pompei, Caroline Moço Erba [UNESP]; Quartaroli, Larissa [UNESP]; Pessi, Bruno Assis [UNESP]; SILVA, GRAZIELE RUAS LAGOAS DA; Silva, Gustavo Henrique Ribeiro [UNESP] (Springer Nature, 2024)
This study utilized vertical tubular photobioreactors featuring mini Biobob® support medium, a cylindrical structure filled with polyurethane foam, providing a surface area of approximately 94,000 m2/m3. The experiment aimed to assess the influence of varying surface area on photobioreactors performance, evaluating treated effluent quality and biomass production. Conducted in a controlled laboratory environment to minimize interference, the reactors were tested in biological duplicates: SBB (no support medium), 1/3BB (67.36 ± 0.01 m2 surface area), and 1/2BB (100.95 ± 0.11 m2 surface area). Inoculated with a native consortium of microalgae and bacteria, the reactors operated semi-continuously with daily feeding of real domestic wastewater, maintaining a hydraulic detention time (HRT) of 5 days. While an increase in attached biomass was observed, it did not markedly enhance wastewater treatment, particularly in nitrogen and phosphorus removal. Nonetheless, the accumulated biomass holds potential for reducing HRT, an avenue for future investigation, and may confer advantages in the separation process, suggesting promising applications for further exploration. This underscores the complexity and potential practical implications of attached biomass phenomena.